Julian Barnes’s England, England: A Literary Portrayal of Individual and Collective Psychosis - Arıkan, Seda; İpekçi, Yeşim (My University, 2020)
Julian Barnes’s England, England (1998) has been widely studied in relation to the concept of Englishness within its social, historical, political, and cultural implications regarding England of the late 20th century. As is foregrounded in this study, the novel places interwoven narratives of the individual and the national self to the centre in order to question their interrelated lack of authenticity. Focusing on the issue of authenticity from the Lacanian psychoanalytic model, this paper specifically seeks to analyse how individual and collective psychosis operate within the novel.
Keywords: Julian Barnes; England; England; Lacanian Psychoanalysis; Psychosis